ANALYSIS OF THE APPLICATION OF OCCUPATIONAL HEALTH AND SAFETY (K3) IN FABRICATION WORK WITH THE RISK ASSESSMENT METHOD AT PT INDUSTRI KERETA KERETA (INKA) BANYUWANGI - Harliwati Prisilia; Dimas Aji Purnomo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Potential hazards always exist when we are doing daily activities and potential hazards always existwherever we are, be it in every place of the work environment or outside the work environment. In the industrialbusiness world, occupational safety and health (K3) is very necessary. There will always be a risk of failure (riskfailures) in every work activity and when a work accident occurs, so that no matter how small the work accidentwill result in a loss effect for both the company and the worker. PT. Industri Kereta Api (INKA) Banyuwangi is astate-owned enterprise engaged in manufacturing services located in Ketapang Village, Kalipuro Banyuwangi. PTINKA Banyuwangi is still relatively newly inaugurated and has just started production, it is not surprising that theattitude of workers towards the application of K3 at PT INKA Banyuwangi has not gone well. The purpose of thisresearch is to identify potential hazards and conduct risk assessment of the level of work accidents at PT INKABanyuwangi.From the results of the identification that occurred at PT. Industri Kereta Api (INKA) Banyuwangi, 10potential hazards and risks were found in field workers. The risk level assessment for field workers contained 3low risks and 5 medium risks. Assessment of risk control in field workers there are 4 mild risks and 4 moderaterisks. While the results of the calculation of risidual risk or residual risk after control efforts are made there are still5 hazard risks that require improvement in work accident control at PT. Railway Industry (INKA) Banyuwangi.